Microscopy investigations of the microstructural change and thermal response of cobalt-based nanoparticles confined inside a carbon nanotube medium1. Issue 21 (7th June 2015) - Baaziz, Walid; Florea, Ileana; Moldovan, Simona; Papaefthimiou, Vasiliki; Zafeiratos, Spyridon; Begin-Colin, Sylvie; Begin, Dominique; Ersen, Ovidiu; Pham-Huu, Cuong
<x xml:space="preserve">Abstract</x> In this work, we investigate the shape, microstructure and thermal response upon heat treatment of Co-based NPs inside CNTs.